2020
DOI: 10.3390/app10207380
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization Effects of Carbon Monoxide Releasing Drugs Chemisorbed on Coscinodiscus Diatoms Carriers Characterized by Spectromicroscopy Imaging

Abstract: Silica microparticles made of diatomaceous earth have become particularly attractive materials for designing drug delivery systems. In order to investigate the use of natural diatoms as drug scaffolds for carbon monoxide releasing molecules (CORMs), we evaluated the chemisorption of the cis-[Re(CO)2Br4]2− complex (ReCORM-2) and its vitamin B12 derivative (B12-ReCORM-2) on Coscinodiscus frustules by 3D FT-IR spectroscopic imaging, and the drugs’ neovascularization effects in vivo in the zebrafish (Danio rerio) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Given the apparent affinity of the fac-[Re(CO)2(NO)] 2+ core for π-donors, we reasoned that fac-[Re I (CO)3(N-N)OR] species might offer us a different chemical approach for the design of an efficient synthetic strategy to fac-[Re(CO)2(NO)(N-N)L] 2+ compounds. Therefore, we decided to test the reaction of fac-[Re I (CO)3(N-N)OR], where OR = OH − , benzoate (10), 2-(4-bromophenyl)acetate (11).…”
Section: Reactivity Of Fac-[re I (Co)3(n-n)or] Species (Or = π-Base) With No +mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the apparent affinity of the fac-[Re(CO)2(NO)] 2+ core for π-donors, we reasoned that fac-[Re I (CO)3(N-N)OR] species might offer us a different chemical approach for the design of an efficient synthetic strategy to fac-[Re(CO)2(NO)(N-N)L] 2+ compounds. Therefore, we decided to test the reaction of fac-[Re I (CO)3(N-N)OR], where OR = OH − , benzoate (10), 2-(4-bromophenyl)acetate (11).…”
Section: Reactivity Of Fac-[re I (Co)3(n-n)or] Species (Or = π-Base) With No +mentioning
confidence: 99%
“…Our group has been interested in the development of the chemistry of tri- and dicarbonyl rhenium complexes for applications in different medicinal fields [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], including their use as antibacterial agents. We recently reported studies on the antimicrobial properties of families of rhenium diimine (N-N) complexes and found several complexes of general formula fac -[Re I (CO) 3 (N-N)L] + (L = pyridine, py, type-ligand), showing low to no toxicity in vivo and potent in vitro and in vivo activity against infection of clinically relevant bacteria (MRSA) and fungi ( Candida species) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Our group has been interested in the chemistry of 18-and 17electron fac-[Re I (CO) 3 ] + and cis-[Re II (CO) 2 ] 2+ species for their potential use in medicinal chemistry, particularly as anticancer [45][46][47][48] and antibacterial agents 26,49,50 and CO-releasing molecules respectively. [51][52][53][54] While abundant literature is available for the biological effects of Re(I) tricarbonyl complexes, very little is known for corresponding Re(I) dicarbonyl species. We, therefore, set out to establish synthetic procedures that would allow accessing the latter core.…”
Section: Introductionmentioning
confidence: 99%
“…42 Our groups are also interested in the chemistry of 18-and 17-electron fac-[Re I (CO) 3 ] + and cis-[Re II (CO) 2 ] 2+ species for their potential use in medicinal chemistry, as anticancer, [44][45][46] CO-releasing and antibacterial agents. [47][48][49] Recently, we reported a study on the antimicrobial properties of a series of 3arylcoumarin rhenium complexes and found that about half of the species investigated exhibit potent in vitro and in vivo activity against MRSA with MICs in the nanomolar range (ca. 350-700 nM in vivo).…”
Section: Introductionmentioning
confidence: 99%